Management of an unusual giant submandibular gland sialolith with a sialo-cutaneous fistula; A case report - Tajrin, Andi; Ritangnga, Rahmad (Journal of Case Reports in Dental Medicine, 2021)
Objective: Sialolithiasis is the most common disease of the salivary glands that can promote sialadenitis and mostly are found in the submandibular gland.1,3 Usually characterized by swelling, pain, infection, and dilation of the salivary duct reduced salivary flow and purulent discharge.2,3 The size may vary from less than 1 mm to a few cm in largest diameter, with most sialoliths being <10 mm in size.2,4We reported a giant submandibular sialolith related to sialo-cutaneous fistula that is likely less commonly reported in the literature.Methods: A 48 old years old male presented with swelling and pain on the left submandibular region since 2 months before the admission, purulent discharges from the fistula near the bulge on the left submandibular area, also from the left floor of the mouth. There was a history of trauma on the swelling are approximately 10 years ago. Computed Tomography (CT) Scan showed the presence of a cylindrical and elongated sialolith located within the Wharton's duct of the left submandibular gland, Panoramic radiograph showed a radiopaque structure superimposed on the left submandibular area. diagno submandibular area. Diagnosis of left submandibular gland sialolithiasis was established. Surgical removal of the sialolith via submandibular approach incision followed by necrotomy of the infected cutaneous fistula was performed under general anesthesia.Results: The extracted sialolith was hard in consistency, brown colored, rounded, and elongated with a dimension of 33 mm long. Administrationof antibiotics, analgetic, and corticosteroid injections during hospitalization for three days after surgery than followed up on day seventh. The patient showed no significant postoperative complications the salivary flow was seen to be normal, and no signs of nerve injuries.Conclusion: Sialolithiasis considered to be the most common salivary gland disease, cutaneous fistula related to a giant submandibular gland sialolithis still less commonly reported in the literature. Conservative treatments are distinctive to small-sized sialoliths. Surgical removal is the treatmentof choice for both trans-oral or submandibular approaches in our present case.